PENDAMPINGAN PEMANFAATAN LEARNING MANAGEMENT SYSTEM DALAM UPAYA PENINGKATAN PEMBELAJARAN DARING PADA SANTRI PONDOK PESANTREN DARUL HIDAYAH - Fitri Utami; Siti Kholijah; Kartika Eka Pertiwi (Jurnal Peduli : Jurnal Pengabdian Kepada Masyarakat, 2023)
Higher education has a very strategic position in producing generations of nations who are globally competitive today and in the future. More specifically, how to build awareness for Islamic boarding school students to continue their education at the tertiary level. At present the opportunity for students to continue their studies in higher education is still very limited. Whereas on the other hand, students have unique characteristics according to the culture of the nation. However, in reality the activities and obligations at Islamic boarding schools cannot be said to be light, so that students need to have mature thoughts in order to be able to assume status as santri students. This service activity aims to provide training to Islamic boarding school students of Darul Hidayah regarding the use of Learning Management System (LMS) media in supporting learning to be more effective and efficient so that they can carry out two roles simultaneously, namely as students and also as students.